O trabalho na indústria têxtil em Itabuna- BA, no contexto da reestruturação produtiva - Souza, Andressa Araújo (2021)
In Brazil, the textile industry adopts the new arrangement for the production process, starting in the 1990s, the spatialization of companies in the Northeast aimed to search for favorable conditions for production and profit. This spatialization is a consequence of the capital accumulation process and the intense adoption of neoliberal policies in the country. The reality of the municipality of Itabuna, a revelation of a population that yearns for formal work as a way of being able to reproduce socially, but that carries the repercussions of transformations in space since the new political and economic conjuncture, such as, for example, the turnover of work, threat of unemployment, extensive workload, and all the strategies that companies create to reduce costs, which imply in the subjects' working conditions. To identify the issues related to the research, it was necessary to have an interview with the current workers, with former workers of the companies, union representatives. With all the information framework, this research aims to analyze a socio-spatial configuration of work in the textile industries Pênalty and Trifil, in the municipality of Itabuna / Ba, in the context of the current phase of capital accumulation; contemporary capitalism, therefore, we seek to use authors who approach the concepts related to the centrality of work, so that an analysis is based on work as a category that is intrinsically linked to human development and autonomy, and not as an element that dehumanizes the subject. The expulsion of workers from the formal labor market, pushes them into precarious working conditions, and force formal workers to submit as pressures exerted inside the factory, with multipurpose and flexible work for the same remuneration, causing companies to continue obtaining high rates of profitability. Thus, the marks found in the new production configuration attract attention, due to the damage they cause to workers.